Um conto, um herói, uma história: do universo maravilhoso das narrativas populares às sagas do sertão na obra Sagarana. - Buhler, Andréa Morais Costa (2012)
This thesis carries out a study on the work of Guimarães Rosa, focusing specifically on three short stories of the book Sagarana which are: São Marcos, A hora e a vez de Augusto Matraga and Conversa de bois. Its objective, at the light of two approaches, takes the hero as a specific category for analysis. The first one has as a fundament the recognition of a formal structure which gives bases to popular narratives as a textual matrix of the selected short stories. The figure of the hero, animated by the sequence fight-test-overcoming, coming from the popular universe, indicates the myth as a speculative and philosophical idea about existence. On the thematic basis of the formal unit of our short stories, we identify the variants of the Menippean satire that directly reassemble the Carnival folklore (the collective time which makes possible the neighborhood of the things and phenomena from where we come from and to where we will go back). The most relevant peculiarity of the Menippean genre that we captured in our profile is the creation of extraordinary situations by the games of oxymorons with the aim of provoking the experimentation of a philosophical idea. The thematic character of the short stories of carnival type is closely connected to the historiccultural system of the common life of the country person. Thus, the second approach intends to follow the cultural and symbolic logic of the socio-historic structure represented, promoting an investigation that ranges from the imaginary of a selected group (beliefs, code of honor ad revenge) to the social relations and conversely. Our analytical path around the work of Sagarana has as the fundamental critical idea the notion that the rosiana art triggers a reflection in which multiple correspondences can come up from a constellation of elements which are apparently disparate. On the selected short stories, we devote ourselves to study how the moral and historical happenings of the country man s life, constructing his vision of the world, intersect with the cyclical character (mythic time) that the work interestedly assumes, creating its artistic unit.